The Kyoto Protocol in the EU European community and member states under international and European law - Massai, Leonardo (T. M. C. Asser Press, 2011)
The participation of the European Community and the Member States in the international climate change regimes is a complex issue. In the case of the Kyoto Protocol, this is rendered more complicated by the fact that, for the purposes of Article 4 of the Kyoto Protocol, the membership of the European Community and Member States is frozen at a particular point in time. The result of this is that, under international law, the European Community and a part of the Member States (EU15) have agreed to jointly fulfill some of those obligations, whereas under community law all Member States share a certain degree of responsibility to meet the obligations created by the Kyoto Protocol. This book analyses in great detail the Kyoto Protocol and the obligations established, such as monitoring and reporting obligations, eligibility criteria and reduction commitments.